Case Report: Significant Clinical Benefit From Pemetrexed-Based Therapy in ROS1- and ALK-rearranged Lung Cancer With Adenosquamous Histology - Patil, Tejas; Nie, Yunan; Aisner, Dara L.; Camidge, David Ross (Frontiers in Oncology, 2022)
Pemetrexed (used as a platinum doublet or as a maintenance regimen) is an established therapy for patients with advanced nonsquamous non-small cell lung cancer (NSCLC). In addition, certain gene rearrangements (ALK, ROS1, RET) appear to especially benefit from the use of pemetrexed. Inferior outcomes with pemetrexed compared to other chemotherapies in patients with NSCLC demonstrating squamous histology removed these patients from the labelled indication for the drug. While most squamous cases do not harbor driver oncogenes, rare exceptions exist. Whether the poor outcomes with pemetrexed extend to NSCLC with squamous component harboring driver oncogenes remains unexplored. In this case series, we describe two patients with squamous and adenosquamous histology harboring an ALK and ROS1 gene arrangement, respectively who derived significant benefit from pemetrexed-based therapy. These cases suggest that the value of pemetrexed may need to be explored in more detail in squamous or adenosquamous NSCLC harboring such alterations.